Idiopathic methicillin-susceptible Staphylococcus aureus associated tricuspid valve endocarditis and pneumothorax in a patient without apparent predisposing factor: a case report - Mohammad Dashtkoohi; Farbod Semnani; Nasser Aghdami; Marjan Sohrabi; Arezoo Salami Khaneshan; Fereshte Ghiasvand; Parnian Adhami Moghadam (Iranian Journal of Microbiology, 2022)
Pneumothorax following right-sided bacterial endocarditis is an infrequent medical complication usually reported in cases with a history of intravenous drug abuse. The following report describes the condition of a girl without congenital heart disease or a history of intravenous drug abuse who developed pneumothorax secondary to endocarditis.